The Association Between Aqueous Connective Tissue Growth Factor and the Severity of Age-related Cataracts as Graded by the Lens Opacities Classification System III. (3rd March 2016) - Hwang, Hyung Bin; Yim, Hye Bin; Cho, Yang Kyung; Choi, Jin A.
ABSTRACT: Purpose : To evaluate the relationship between aqueous humor concentrations of connective tissue growth factor (CTGF) and the severity of age-related cataracts. Materials and Methods : We conducted a prospective clinical study on 43 eyes of 43 patients with senile cataracts scheduled to undergo routine phacoemulsification surgery. Before surgery, all patients were graded for cataract severity using the Lens Opacities Classification System III in terms of four features: nuclear opalescence (NO), nuclear color (NC), cortical cataracts (C), and posterior sub-capsular cataracts (P). During surgery, aqueous humor samples were obtained from all patients, and sandwich enzyme-linked immunosorbent assays (ELISAs) were used to determine CTGF concentrations. To assess any relationship between cataract severity and CTGF levels of the aqueous humor, various correlation analyses and multiple linear regression were used. Results : We found a positive correlation between the overall cataract grade and aqueous CTGF level ( p < 0.05). In addition, four features of the cataract grade (nuclear opalescence, nuclear color, cortical cataract and posterior sub-capsular cataract) were positively correlated with the aqueous CTGF concentration ( p < 0.05). The final regression model identified overall cataract grade as an independent predictor of increased CTGF levels in the aqueous humor ( p < 0.05). Conclusions : CTGF tends to increase in the aqueous humor as the severity of age-related cataracts increases. Therefore, this cytokine may play an important role in the pathogenesis of age-related cataracts. Additional studies are required for clarification of this finding.